Bringing Transdisciplinary Aging Research From Theory to Practice. (22nd December 2020) - Sargent, Lana; Slattum, Patricia; Brooks, Marshall; Gendron, Tracey; Mackiewicz, Marissa; Diallo, Ana; Waters, Leland; Winship, Jodi; Battle, Kimberly; Ford, Gregory; Falls, Katherine; Chung, Jane; et al.
Abstract: There is a growing emphasis to use a transdisciplinary team approach to accelerate innovations in science to solve complex conditions associated with aging. However, the optimal organizational structure and process for how to accomplish transdisciplinary team science is unclear. In this forum, we illustrate our team's experience using transdisciplinary approaches to solve challenging and persistent problems for older adults living in urban communities. We describe our challenges and successes using the National Institutes of Health four-phase model of transdisciplinary team-based research. Using a de-identified survey, the team conducted an internal evaluation to identify features that created challenges including structural incongruities, interprofessional blind spots, group function, and group dynamics. This work resulted in the creation of the team's Transdisciplinary Conceptual Model. This model became essential to understanding the complex interplay between societal factors, community partners, and academic partners. Conducting internal evaluations of transdisciplinary team processes is integral for teams to move beyond the multi- and interdisciplinary niche and to reach true transdisciplinary success. More research is needed to develop measures that assess team transdisciplinary integration. Once the process of transdisciplinary integration can be reliably assessed, the next step would be to determine the impact of transdisciplinary team science initiatives on aging communities.